Towards territorial development in fisheries areas: A typology of projects funded by Fisheries Local Action Groups - Miret-Pastor, Lluís; Svels, Kristina; Freeman, Richard (Elsevier Science Ltd., 2020)
Community-led Local Development (CLLD) offers a novel bottom-up approach to achieving territorial development in EU fisheries and aquaculture areas. Through Fisheries Local Action Groups (FLAGs), CLLD sets out to increase both employment and territorial cohesion by bringing together local stakeholders in the selection and implementation of projects which meet the specific needs of the FLAG area and its fisheries communities. Through an analysis of 2691 FLAG projects, this study offers comparative insights into the implementation of CLLD across eight EU Member States. The analysis shows that there are three areas that account for almost 90% of total budget spending, projects attributed to adding value to the fisheries value chain, the diversification fisheries activities, and those with socio-cultural focus, while fewer projects attributed to the environment or increasing representation in local governance. The results of this analysis are compared with the priorities expressed by FLAGs at the beginning of the program, as well as the national Operational Programs of individual Member States.
Keywords: small-scale fisheries; community-led local development; fisheries local action groups; fisheries diversification; neo-endogenous develpment; kalastuspolitiikka